Empowering Educators: Technical Insights into the Integration of Information and Communication Technology in Teacher Training (International Journal of Food and Nutritional Sciences, 2022)
Today, we are living in a knowledge based society, and knowledge-based global world where knowledge is a great power, economy and strength of an individual, and the asset of a nation. It is also true that these are in tremendous explosion in its quality as well as growth. We are in need of new technologies to have access and proper use of this fast growing knowledge. Moreover, a mere acquisition of knowledge is not enough; we have a complete access and mastery over the knowledge getting process. It can only happen with the assistance of the science of information and communication technology. In this chapter, we would be knowing some essentials about the nature and how for useful of information and communication technology in the field of teacher education sector.